2021
DOI: 10.3389/fpsyg.2021.720199
|View full text |Cite
|
Sign up to set email alerts
|

Confirming the Reliability and Validity of the Sexual Minority Adolescent Stress Inventory in a National Sample of Sexual Minority Adolescents

Abstract: Objective: Sexual minority adolescents (SMA) experience numerous behavioral health disparities, including depression, anxiety, substance use, non-suicidal self-injury, and suicidality. The primary framework to understand these disparities is minority stress theory, which frames this disproportionate burden as the result of discrimination, violence, and victimization in a homophobic culture. Empirical examinations of minority stress among SMA have been limited by lack of diverse samples or validated measures. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Items included in the SMASI are based on key minority stress theory frameworks (Goldbach et al, 2014;Hatzenbuehler, 2011;Meyer, 2003) and qualitative information obtained via interviews with sexual minority cisgender adolescents ages 13-19 years. Schrager et al ( 2018) and Goldbach et al's (2017) initial validation studies as well as Goldbach et al's (2021) follow-up validation study with a diverse sample demonstrated the SMASI scales had strong internal consistency reliability and good divergent and convergent validity with other mental health measures. Additionally, Burgess (2017) and Fulginiti et al (2020) found the SAMSI to be psychometrically sound in their respective studies.…”
Section: Methodsmentioning
confidence: 99%
“…Items included in the SMASI are based on key minority stress theory frameworks (Goldbach et al, 2014;Hatzenbuehler, 2011;Meyer, 2003) and qualitative information obtained via interviews with sexual minority cisgender adolescents ages 13-19 years. Schrager et al ( 2018) and Goldbach et al's (2017) initial validation studies as well as Goldbach et al's (2021) follow-up validation study with a diverse sample demonstrated the SMASI scales had strong internal consistency reliability and good divergent and convergent validity with other mental health measures. Additionally, Burgess (2017) and Fulginiti et al (2020) found the SAMSI to be psychometrically sound in their respective studies.…”
Section: Methodsmentioning
confidence: 99%
“…Lifetime experiences of adolescent minority stress were assessed with 10 subscales of the SMASI. 56 Subscales included items like "I have been physically assaulted in the neighborhood where I live because I am LGBTQ," "A religious leader tried to change my sexual orientation," and "My parents are uncomfortable with LGBTQ people," with binary response options (0 = no, 1 = yes). Higher percentages reflected more lifetime experiences of minority stress.…”
Section: Lifetime Experiences Of Adolescent Minority Stressmentioning
confidence: 99%